The Development of Conceptual Model for Green Marketing Performance - Aritonang Rajagukguk, Sabar (International Journal of Innovation Research in Education, Technology and Management, 2025)
Electric vehicles are seen as one of the most significant solutions to the problem of climate change. Various innovative efforts made by the company have not provided optimal results. It has long been understood that innovation is controlled internally by the company until the theory of service-dominant logic provides a new paradigm that value can be created with customers. However, no one has shown the urgency and significance of education to the target market as an important mediator to create the company's innovation capability. Using the service-dominant logic theory as well as 38 empirical research articles, a conceptual model was found to fill the research gap. The conceptual model includes education to the target market as a mediator between the company's commitment to creating electric vehicles and the company's innovation capability on marketing performance.